Социально-психологические факторы удовлетворённости выбранной профессией будущими инженерами - Шульга, А. В. (НТУ "ХПИ", 2014)
Статья посвящена рассмотрению и систематизации результатов исследований удовлетворённости выбранной профессией студентов различных специальностей. Рассмотрены факторы, влияющие на удовлетворённость профессиональным выбором. Описаны возможные методы, способствующие профессиональному самоопределению школьников и повышению уверенности в правильности выбора профессии у студентов.

The article is devoted to consideration and systematization the results of satisfaction surveys of chosen profession by students of different specialties. Describes the factors that affect to the satisfaction of professional choice. Describes the possible methods that promote professional self-determination of schoolchildren and increase confidence in the correctness of the choice of profession among students.
Socio-psychological satisfaction factors of chosen profession by future engineers
Keywords: самоопределение профессиональное; профориентация; продуктивность; profession satisfaction; professional self-determination; career guidance